Teacher Analysis Study According to Imam Al Ghazali in the Book of Al Adab Fi Al-Din - Aryanti, Yosi; Mutathahirin, Mutathahirin; Rahman, Ikhwan; Mulyani, Ridha (STIT Ahlussunnah Bukittinggi, 2022)
Imam Al Ghazali is the only great Islamic scholar who is nick named Islamic document because of his enormous influence in various Islamic sciences, starting from theology, philosophy, jurisprudence, sufism and ethics. Regarding ethics, imam has a work that discusses it specifically, namely the book al-Adab fi al-Din. Among the ethics discussed in the book al-Adab fi al-Dinis teacher ethics. This research aims to analyze the ethics of a teacher according to Imam al-Ghazali. This research is descriptive research using the library method library research, this research approach uses a descriptive analysis approach, namely by collecting, compiling, and analyzing interpretations or interpretations in the book al-Adab fi al-Din chapter adab Muallimi al-Shibyanwhich discusses teacher ethics in teaching students. Data collection and data analysis were carried out by reviewing related books and books to obtain more accurate information. The research results show that the book al-Adab fi al-Din chapter Adab Muallimi al-Shibyan this work by Imam Al-Ghazali explains: First, teacher ethics according to Imam Ghazali in the book al-Adab fi al-Din bab Adab Muallimi ash-Shibyan consists of two concepts, namely; teacher personal ethics and teacher interaction ethics. Regarding teachers' personal ethics, Imam al-Ghazali put forward a keyword, namely improving oneself, because the aim of education is not only to make students smart but more than that, education is to make them true individuals and, a teacher can't make his students become righteous individuals if their own personalities are crooked. Meanwhile, regarding the ethics of teacher interaction, Imam al-Ghazali places great emphasis on three things, namely; objective, professional, andtawassuth, second, everything that Imam al-Ghazali explained regarding teachers' personal ethics and their ethics in interacting with students feels very current and relevant to the current conditions of education and educators, because what Imam Al Ghazali wrote are things that are universal and apply throughout time. What was problematic and problematic at that time, is also happening now, with the substance of the same problem, even though the context is different.